Relasi Akal dan Hati menurut al-Ghazali - Ahmad Arisatul Cholik (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
In Western intellectual tradition, ratio has been seen all this time not only as the source of knowledge but also human behavior. This tradition formed the view toward knowledge which raised rationalism and number of Western school of thought up that become the principle of Western civilization up to now. This view is certainly different with Islamic tradition, when ratio could not be separated from heart as a substance knowing rational problems, empiric, or metaphysics. It means that in the view of Islam, truth is not limited in the physical realm but in metaphysic as well. Therefore, knowledge produced from ratio should be related carefully to heart. According to al-Ghazali, ratio and heart could not be separated each other as these substance could not be separated from another substances. The relation between ratio and heart actually led human to the truth. Al-Ghazali’s statement about this relation in fact begun from his view about dimension of soul, that became the source of physical dimension of human in psychological context, motored by ‘aql and qalb. In this paper, writer concluded that: first, ‘aql and qalb are smooth and soft; second, ‘aql is only limited to the issue of intelligence, when qalb also able to reach truth in spiritual matters as well; the heart’s capability to reach a metaphysical realm is always supported by rational knowledge, but this knowledge is not enough to avoid qalb from mistakes except by accepting religious knowledge that came from the prophets.